Design and Electromagnetic Analysis of a New Rotary-Linear Switched Reluctance Motor in Static Mode - Nezamabadi, M. M.; Afjei, E.; Torkaman, H. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A newly designed rotary-linear switched reluctance (RLSRM) motor is presented and electromagnetically analyzed in this paper. The motor has an integrated structure and can control both linear and rotary motions. It is mainly designed to control the engagement of a rotating gear. For this purpose a twosection motor comprised of a rotary and a linear SRM is designed. In the middle part of the motor assembly, a three-phase rotary SRM with 6 stator and 4 rotor poles creates rotary motion. The linear section which is a transverse flux two-phase SRM is composed of two parts placing at each side of the rotary section. The cylindrical translators inside the linear stator poles provide short magnetic flux paths which reduce the core losses and increase the force per volume. The motor parameters derived from the motor design procedure are evaluated using 3-dimensional finite element analysis (3DFEA). The motor performance indices such as flux linkages, flux density, mutual flux, static torque and force for various loads are obtained and assessed for rotary and linear motions. Finally, a comparative study is performed and 3DFEA results are compared with two different RLSRM structures. The comparison shows that the proposed structure has the highest force per motor volume.